AB INITIO STUDY OF AMMONIA CLUSTERS: (NH3)n (n = 2-6) - Herudi Kandau; Hanggara Sudrajat; Andreas Napitupulu; Syahrul Khairi; Zaky Al-Fatony; Herman Siagian (Indonesian Journal of Chemistry, 2008)
Hydrogen bonded neutral clusters of ammonia, (NH3)n (n = 2-6), have been theoretically investigated employing the D95++(d,p) (and wherever necessary, higher) basis sets at the Hartree-Fock (HF) level as well as with second-order Møller-Plesset (MP2) perturbation theory. While the ammonia trimer and tetramer exhibit perfect molecular symmetries and are nonpolar, the pentamer and hexamer both optimize with slight deviations from perfect symmetries and are seen to posses marginal, but nonzero dipole moments. The (NH3)n linear clusters are seen to be chemically softer than the corresponding cyclic ones.